Database Management of Vedaranyam Taluk, Nagappattinam District, Tamilnadu using Geographic Information System (GIS) - S. Tamilenthi*, G. Thilagavathi, R. Baskaran, C. Ramu (Recent Research in Science and Technology, 2011)
GIS, known as geographical information system, is the latest tool, a computer system for capturing, storing, checking, integrating, manipulating, analysis in and displacing data related to positions on the Earth’s surface. Typically, a geographical information system or (spatial information system) is used for handling maps of one or another. These might be represented as several different layers each layer holds about a particular kind of feature is linked to a position on the graphically image of a map. With the help of GIS a data base management including data or demography, occupation, education, health, drinking water, power, telecommunication, roads/transportation, banks& commercial institutions, agriculture, sanitation, common property resources ,employment, forestry, industries, marketing facilities, etc. The scope of the work involves 1, data pertaining to geological and geophysical resources, human resources, social and economic infrastructure, etc. should be collected, collected, updated, and retrieval on regular basis, 2, generation of real time, reliable database on natural resources, socio-economic, agro- climatic condition, financial, institutional and environmental data using geo- informatics and 3, data base to cater to the needs of planning sharing information to various user organizations with necessary data analysis, etc and would act as a centralized data base for state govt. department/ institutions/ institutions involved in development planning.